The Integration of Science and Spirituality: A Comparative Study of the Thought of Ismail Raji al-Faruqi and Seyyed Hossein Nasr - Muhlas, Muhlas; Abdul Gani, Cr. Siti Fatimah Binti; Kusnawan, Aep; Naan, Naan; Negara, Muhammad Adress Prawira (FIKRAH, 2025)
Scholarly discourse on contemporary Muslim scholars has developed rapidly, both emerging from Islamic sources and adopted from other sources. The ideas of science are interesting subjects to be studied further, especially themes related to science and spirituality which are seen as separate from each other.This article examines the integration of knowledge and spirituality through a comparative analysis of the ideas of Ismail Raji al-Faruqi and Seyyed Hossein Nasr. The study aims to explain how both scholars understand the relationship between knowledge and spiritual values, as well as to identify their contributions to contemporary discourses on the integration of knowledge. This research employs a qualitative, library-based approach by collecting data from the primary works of both thinkers and relevant secondary academic literature, which are then analyzed using descriptive-comparative and interpretative methods. The findings show that al-Faruqi emphasizes the Islamization of knowledge as an epistemological framework rooted in the principle of tawhid, whereas Nasr highlights the importance of reviving sacred knowledge and metaphysical foundations as a response to the epistemic crisis of modernity. Both scholars reject the secular separation between knowledge and spirituality, yet they differ in methodological orientation: al-Faruqi focuses on epistemological reconstruction, while Nasr stresses the restoration of spiritual and metaphysical dimensions. The contribution of this research lies in its analytical and systematic comparative mapping of the two thinkers’ approaches to integrating knowledge and spirituality within the context of modern intellectual challenges.